Reduce Manufacturing Lead Time Through PDCA And Waste Elimination In Metal Casting Company: A Case Study - Azhan, Anis Masturina (Universiti Sains Malaysia, 2022)
In the late 1900s and early 2000s, there were a few newly founded foundries that were better organized and used contemporary machinery to make high-quality iron and steel castings in small and medium-sized enterprises (SMEs). The late delivery of a particular product was one of the most important challenges experienced by foundry experts and researchers throughout manufacturing. Consequently, the customer experienced unsatisfactory service. Utilizing the PDCA continuous improvement cycle is necessary since it is a crucial tool for raising the quality of a product over time and minimizing waste. To save time, it was used in an attempt in this thesis study. The major purpose of this thesis is to reduce the manufacturing lead time of metal casting using the PDCA cycle and waste elimination in the administration department. The potential waste that might occur during the manufacturing lead time has been identified via a review of the relevant literature and the implementation of fishbone diagrams in the root cause analysis step. Then, as a potential countermeasure, the WITNESS Horizon simulation was used to examine and compare production line models with and without motion waste. This thesis found that the simulation model 3 showed the lowest lead-time compared to simulation model 1 and 2 with the elimination of all motion waste at the discussion section. It can be concluded that with the implementation of PDCA cycle in this thesis, the lead-time of metal casting process has been improved by 4.34% systematically. It was proven that the PDCA cycle is an excellent tool to reduce the metal casting process.